MARINE FOSSILS OF 30-40ka IN RAISED BEACH DEPOSITS, AND LATE PLEISTOCENE GLACIAL HISTORY AROUND LUTZOW-HOLM BAY, EAST ANTARCTICA - イガラシ, アツオ; ハラダ, ナオミ; モリワキ, キイチ; IGARASHI, Atsuo; HARADA, Naomi; MORIWAKI, Kiichi (National Institute of Polar Research, 1995)
P(論文) Radiocarbon ages of fossil marine organisms in raised beach deposits along the Soya Coast are clearly classified into two groups of 3-8ka and 33-42ka by Tandetron Accelerator Mass Spectrometry (TAMS). The older fossils are recognized on the Ongul Islands and the northernmost part of Langhovde, which are separated from the present ice sheet margin by a drowned glacial trough deeper than 500m. Some of the older molluscan fossils as well as the younger ones retain their living form in situ. These facts together with the deep continental shelf and a small amount of isostatic uplift of the Holocene raised beaches lead to the following conclusions for the region : 1) Marine transgression took place in the last interstadial and in the Holocene. 2) Major deglaciation took place by the last interstadial in the region. 3) Expansion of the ice sheet during the Last Glacial Maximum was slight, although its extent is still unknown. 4) Sea-level during the last interstadial was probably higher than that estimated from foraminiferal δ^<18>O records in deep-sea sediments. departmental bulletin paper